Gα(13) Switch Region 2 Binds to the Talin Head Domain and Activates αIIbβ3 Integrin in Human Platelets - Srinivasan, Subhashini (J Biol Chem, 2015)
Even though GPCR signaling in human platelets is directly involved in hemostasis and thrombus formation, the sequence of events by which G protein activation leads to αIIbβ3 integrin activation (inside-out signaling) is not clearly defined. We previously demonstrated that a conformationally sensitive domain of one G protein, i.e. Gα(13) switch region 1 (Gα(13)SR1), can directly participate in the platelet inside-out signaling process. Interestingly however, the dependence on Gα(13)SR1 signaling was limited to PAR1 receptors, and did not involve signaling through other important platelet GPCRs. Based on the limited scope of this involvement, and the known importance of G(13) in hemostasis and thrombosis, the present study examined whether signaling through another switch region of G(13), i.e. Gα(13) switch region 2 (Gα(13)SR2) may represent a more global mechanism of platelet activation. Using multiple experimental approaches, our results demonstrate that Gα(13)SR2 forms a bi-molecular complex with the head domain of talin and thereby promotes β3 integrin activation. Moreover, additional studies provided evidence that Gα(13)SR2 is not constitutively associated with talin in unactivated platelets, but becomes bound to talin in response to elevated intraplatelet calcium levels. Collectively, these findings provide evidence for a novel paradigm of inside-out signaling in platelets, whereby β3 integrin activation involves the direct binding of the talin head domain to the switch region 2 sequence of the Gα(13) subunit.